THE LINK OF CURRENT RATIO, BENCHMARK COAL PRICE, RETURN ON ASSETS, AND DEBT TO EQUITY RATIO TO CASH HOLDING: THE CASE OF ADARO ENERGY TBK IN 2018 – 2022 - William Ben Gunawan (UNKLAB Business School, 2023)
In the modern era of financial management, effective cash management plays a critical role in ensuring the stability and growth of companies across various industries. Understanding the factors that influence cash holdings has become a subject of substantial interest for researchers and practitioners alike. This study aims to explore the intricate relationship between four key financial variables, namely the current ratio, coal price index, debt to equity ratio, and return on assets, and their impact on the cash holding decisions of PT Adaro Energy Indonesia during the 2018 – 2022 financial years. By examining these interrelated factors, this paper offers valuable insights into the dynamics of corporate cash management, providing a foundation for strategic financial planning and decision-making. The results of the study found that all independent variables have a simultaneous but no partial effect on cash holding. Keywords: benchmark coal price, cash holding, current ratio, debt to equity, return on asset Di era modern manajemen keuangan, manajemen kas yang efektif memainkan peran penting dalam memastikan stabilitas dan pertumbuhan perusahaan di berbagai industri. Memahami faktor-faktor yang mempengaruhi kepemilikan uang tunai telah menjadi subjek yang sangat menarik bagi para peneliti dan praktisi. Penelitian ini bertujuan untuk mengeksplorasi hubungan rumit antara empat variabel keuangan utama, yaitu rasio lancar, indeks harga batubara, rasio utang terhadap ekuitas, dan pengembalian aset, dan dampaknya terhadap keputusan kepemilikan kas PT Adaro Energy Indonesia Tbk pada tahun 2018 – 2022. Dengan memeriksa faktor-faktor yang saling terkait ini, makalah ini menawarkan wawasan berharga tentang dinamika manajemen kas perusahaan, memberikan landasan bagi perencanaan keuangan strategis dan pengambilan keputusan. Hasil penelitian menemukan bahwa semua variabel independen memiliki efek simultan tetapi tidak parsial terhadap kepemilikan kas. Kata Kunci: harga batubara acuan, kepemilikan kas, rasio lancar, debt to equity, return on asset